Internal waterproofing acrylic back grouting and composite reinforcement method, and Concrete structure waterproofing reinforcement system using the same
Patent Information
- Application Number
- KR1020250172444
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-11-14
Smart Images

Figure 112025127593918-PAT00011_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a two-component acrylic waterproofing injection and an inner waterproof acrylic back grouting composite reinforcement method for waterproofing reinforcing guide plate joints by applying a back grouting method and a guide waterproofing method together when reinforcing the waterproofing of ceilings, walls, pipes, and auxiliary structures (structures constructed connected to ceilings and walls) of concrete structures, and a waterproofing reinforcement system for concrete structures using the same. Background Technology
[0003] Generally, to repair leakage caused by cracks or deterioration in concrete structures, various methods are used, such as using an organic synthetic polymer resin-based sealant that is reactive with water, like water-foamed urethane or water-soluble epoxy, or using an inorganic sealant that has water-soluble rubber admixtures such as acrylic, ethylene-vinyl acetate (EVA), or styrene-butadiene rubber (SBR) added to cement, or using a sealant that has bentonite mineral particles with the characteristic of increasing volume upon reaction with water, added to organic compounds such as asphalt, urethane, or epoxy resin, or to an inorganic mixture that has water-soluble rubber admixtures such as acrylic, EVA, or SBR added to cement, and then forcibly injecting it into the back surface of the concrete structure to cure, foam, or swell.
[0004] However, while water-reactive organic synthetic polymer resin-based waterproofing materials such as water-foaming urethane and water-soluble epoxy initially exhibit excellent waterproofing effects through foaming or curing, their effectiveness gradually declines over time due to shrinkage, leading to reduced long-term durability. In particular, organic synthetic polymer products generally have poor resistance to alkali, resulting in detachment at the interface adhering to the concrete surface caused by strong alkaline solutions such as sodium hydroxide, calcium hydroxide, and potassium hydroxide that dissolve and leach out of the concrete, leading to leakage within a short period.
[0005] In addition, inorganic waterproofing materials, which are cement mixed with water-soluble rubber admixtures such as acrylic, EVA, and SBR, lack adhesion to concrete structures. When injected into the back of concrete, if leakage is excessive, they dissolve in water before hardening, failing to exhibit proper strength, and there were problems with recurring leakage as cracks formed due to drying shrinkage.
[0006] Furthermore, existing one-component repair and reinforcement injection agents suffer from water migration into internal concrete leakage areas, leading to the destruction of the waterproofing layer due to moisture evaporation, as well as performance degradation during the shrinkage, expansion, and drying processes of the chemical solution. Additionally, due to the short curing time, long-distance penetration is impossible, posing a problem in that the fundamental leakage areas cannot be sealed. Prior art literature
[0008] Korean Registered Patent No. 10-0948348 (Publication Date: March 22, 2010) Korean Registered Patent No. 10-1845451 (Publication Date: April 5, 2018) Korean Registered Patent No. 10-0413228 (Publication Date: December 16, 2003) Korean Registration No. 10-1590345 (Publication Date: February 1, 2016) The problem to be solved
[0009] The present invention aims to provide an inner water-blocking acrylic back grouting and composite reinforcement method by introducing a back grouting method using a two-component acrylic back waterproofing liquid to address the disadvantages of existing underground waterproofing methods, such as durability issues, the occurrence of concrete neutralization reactions due to acidic (epoxy) materials, and the method of waterproofing only the leaking area rather than blocking the source of the leak. Additionally, since back grouting is impossible due to pipes and ceiling structures, guide plate waterproofing is performed to control the water flow. Furthermore, the invention provides a guide waterproofing method using a durable grid fiber reinforcement sheet instead of silicone for the joints that can respond to water pooling caused by the unevenness of the plates when installing the guide plate water guide.
[0010] More specifically, the inventors have developed a two-component acrylic back grouting, but since elasticity and tensile strength were somewhat lacking at high temperatures of 50°C or higher, there was a tendency for long-term performance stability to be somewhat poor. Therefore, the inventors intend to provide an inner waterproof acrylic back grouting and composite reinforcement method by introducing a new acrylic mixed resin and a rapid-setting agent component into the main one-component material, and a waterproofing reinforcement system for concrete structures using the same. means of solving the problem
[0012] The composite reinforcement method of the present invention for achieving the above objective is a waterproofing method that performs back grouting and guided waterproofing together. As a back waterproofing agent, the back grouting method is performed using a two-component acrylic waterproofing grout material, and the joint is repaired and reinforced using the guided waterproofing method using an EVA-based coating material and a grid fiber reinforcement sheet. Effects of the invention
[0014] The back grouting method of the present invention is a fundamental waterproofing method that forms a new waterproof layer by injecting a two-component acrylic waterproofing grout material with high elasticity and tensile strength at ultra-high pressure to penetrate around the fundamental leakage site. By applying an EVA-based coating material and a specially processed non-woven sheet instead of the conventional silicone finish to the joints created when installing guide waterproofing panels, a robust repair layer is formed over a long period. This provides appropriate elasticity and tensile strength capable of effectively responding to cracks and movement, thereby guaranteeing a semi-permanent lifespan with a single repair and reinforcement process. Furthermore, it can be applied not only to the joints of guide waterproofing panels but also to inter-floor joints, joints of other structures, and window frame joints, and allows for customized crack reinforcement according to the width and length of the crack. Brief explanation of the drawing
[0016] Figure 1 shows a schematic process diagram of the inner surface water-blocking acrylic-based back grouting composite reinforcement method of the present invention. Specific details for implementing the invention
[0017] The present invention will be described in more detail below.
[0018] The inner surface waterproofing acrylic back grouting composite reinforcement method of the present invention is a waterproofing repair method that performs back grouting and guided waterproofing together. It performs back grouting using a back waterproofing liquid containing a two-component acrylic waterproofing grout material, and repairs and reinforces the joints using an guided waterproofing method using an EVA-based coating material and a specially processed non-woven fabric sheet (e.g., a grid fiber reinforcement sheet).
[0019] The above back grouting method is explained as follows.
[0020] As shown in the schematic process diagram in FIG. 1, the back grouting method performs a process including: Step 1-1, preparing the surface of the construction area where cracks have occurred; Step 1-2, drilling and installing packers in the prepared construction area; Step 1-3, filling the inside of the cracks by injecting back cutoff liquid at high pressure through the packers; and Step 1-4, removing the packers after filling is complete and then finishing treatment.
[0021] To describe a desirable specific embodiment of this, first, in step 1-1, the location of reinforcing bars and pipes is identified to confirm the construction area where cracks or other issues have occurred and the location for drilling therein, and then foreign matter around the construction area to be drilled is removed. At this time, the construction area where cracks have occurred in step 1-1 may be the ceiling, wall, or floor of the structure.
[0022] Next, for the first two stages of drilling, drill to a depth of 200mm to 300mm in the base material when repairing leak cracks, and drill up to the waterproofing layer when performing backfill grouting. Additionally, for leak crack repair, drill one hole every 0.5m, and for backfill grouting, drill one hole every approximately 1m or 1m². At this time, the drilling pattern for each structure is applied on-site to adjust the depth to facilitate injection. Next, after thoroughly cleaning the area around the drilled holes to ensure there is no foreign matter, install injection packers.
[0023] In addition, to prevent backflow and leakage of the backwater cutoff liquid, it is recommended to treat vulnerable areas around the repair site with a sealing material using the POUR crack repair method. Also, after installing the packer, if a large amount of groundwater flows out from the back, leave it open until the amount of water flows out.
[0024] Next, in steps 1-3, the main component of the two-component backwater barrier and the hardener component are added to and mixed in an injection tank, and an accelerator and / or water may also be added. Then, the mixed two-component acrylic waterproofing grout material (backwater barrier) can be prepared by adjusting the viscosity, i.e., the gel type, according to the amount of leakage and sufficiently diluting it with water. Furthermore, the injection of the backwater barrier is carried out by varying the injection amount and range according to the injection pressure and the state of leakage.
[0025] Next, once the backwater blocking liquid filling is completed in steps 1-4, the injection port is sealed and then cut and removed in the same manner as the work surface. At this time, when removing the packer, seal the injection port with quick-setting cement paste or high-viscosity epoxy to finish the coating.
[0027] The above back-side fluid of steps 1-3 is explained as follows.
[0028] The above backwater barrier may be a two-component backwater barrier available in the industry, and preferably, a two-component acrylic waterproof grout material may be used.
[0029] The above two-component acrylic waterproofing grout material includes a first component as the main material and a second component as the hardener component.
[0030] And, the above-mentioned first-component formulation comprises an acrylic mixed resin, an inorganic binder, a quick-setting agent, a powdered silicone water repellent, an anti-shrinkage agent, and an anti-foaming agent, preferably comprising 35 to 48 wt% acrylic mixed resin, 4.0 to 8.0 wt% bonding promoter, 1.0 to 3.0 wt% physical property enhancer, 1.0 to 4.0 wt% powdered silicone water repellent, 0.5 to 1.7 wt% shrinkage preventer, 0.1 to 1.0 wt% anti-foaming agent, and the remaining amount of an inorganic binder out of 100 wt%, more preferably comprising 37 to 44 wt% acrylic mixed resin, 4.5 to 7.0 wt% bonding promoter, 1.2 to 2.0 wt% physical property enhancer, 1.5 to 2.5 wt% powdered silicone water repellent, 0.7 to 1.3 wt% shrinkage preventer, 0.2 to 0.5 wt% anti-foaming agent, and 100 It includes the remaining amount of inorganic binder in weight%.
[0032] Among the components of the first-component formulation, the above acrylic mixed resin may include an acrylic copolymer in which an alkyl (meth)acrylate containing an alkoxysilyl group (meth)acrylate and a (meth)acrylate containing a dicyclic structure are copolymerized; a polyfunctional monomer; and a glycidyl acrylic monomer.
[0033] The above acrylic copolymer is a copolymer of an alkyl (meth)acrylate, an alkoxysilyl group-containing (meth)acrylate, and a cycloaliphatic structure-containing (meth)acrylate, and may be, for example, a random copolymer.
[0034] The above alkyl (meth)acrylate may be an alkyl (meth)acrylate known in the art, and as an example, may be an alkyl group (meth)acrylate having 1 to 14 carbon atoms. More specifically, the above alkyl (meth)acrylate may be, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, iso-octyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, etc. Preferably, the alkyl (meth)acrylate may be an alkyl (meth)acrylate having 1 to 2 carbon atoms, more preferably a methyl (meth)acrylate, and even more preferably a methyl methacrylate, which may be advantageous for achieving the purpose of the present invention.
[0035] In addition, the alkoxysilyl group-containing (meth)acrylate prevents moisture penetration and prevents the cured body, polymerized from acrylic copolymers and / or acrylic monomers described later, from decomposing or being damaged by moisture, and can perform the function of preventing or minimizing moisture damage to the inorganic binder provided together with the first agent. Preferably, the alkoxysilyl group-containing (meth)acrylate may be 3-(trimethoxysilyl)propyl methacrylate, which is advantageous for further improving moisture penetration prevention and durability by exhibiting a synergistic effect with the alicyclic structure-containing (meth)acrylate described later.
[0036] In addition, the above-mentioned (meth)acrylate containing a cycloaliphatic structure can improve the water resistance and durability of the acrylic copolymer and prevent a significant increase in viscosity, thereby increasing penetration into fine gaps formed in cracks. The above-mentioned (meth)acrylate containing a cycloaliphatic structure can be used without limitation as long as it has a cycloaliphatic structure within the (meth)acrylic monomer, and as an example, it may include one or more selected from the group consisting of cyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate, 4-tert-butylcyclohexyl acrylate, dicyclopentenyloxyethyl methacrylate and isobornyl acrylate, and 1-adamantyl (meth)acrylate, and more preferably, it may include dicyclopentenyloxyethyl methacrylate.
[0037] In addition, the acrylic copolymer may more preferably be a random copolymer in which methyl (meth)acrylate, 3-(trimethoxysilyl)propyl methacrylate, and dicyclopentenyloxyethyl methacrylate are copolymerized in a molar ratio of 1:0.4 to 0.6:0.8 to 1.0, and may have a weight-average molecular weight of 6,000 to 12,000, which may be more advantageous for achieving the objectives of the present invention.
[0038] In addition, polyfunctional monomers and glycidyl acrylic monomers are described as monomers included together with the acrylic copolymer described above.
[0039] The above-mentioned polyfunctional monomer increases the crosslinking density of the polymerized and cured body formed from an acrylic resin mixture, thereby maintaining durability for a long time even when partial damage occurs due to moisture penetration; preferably, it may be a diacrylic monomer containing two acryloyl groups. If the polyfunctional monomer contains more than two acryloyl groups, the elasticity may decrease as the crosslinking density becomes excessively high, and there is a risk that long-term durability may actually decrease as a result. The above-mentioned diacrylate monomer may be used without limitation if it contains two acryloyl groups within a monomer known in the art, and examples include 1,4-butanediol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate (HDDA), 1,8-octanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, cyclohexane-1,4-dimethanol di(meth)acrylate, tricyclodecanedimethanol (meth)diacrylate, and dimethylol dicyclopentane di(meth)acrylate. It may include one or more selected from the group consisting of neopentyl glycol modified trimethylpropane di(meth)acrylate, adamantane di(meth)acrylate, and diacrylic compounds represented by the following chemical formula 1, and more preferably may be a compound represented by the following chemical formula 1, thereby exhibiting a synergistic effect with the acrylic copolymer described above, which may be advantageous for achieving the objective of the present invention.
[0040] [Chemical Formula 1]
[0041]
[0042] In Chemical Formula 1, R 1 and R 2Each is independent and is -CHCH2, -CH2CHCH2, -CH2CH2CHCH2 or -CH2CH(CH2CHCH2)CH3, preferably -CH2CH2CHCH2 or -CH2CH(CH2CHCH2)CH3, more preferably or -CH2CH(CH2CHCH2)CH3.
[0043] In addition, the polyfunctional monomer, such as a diacrylate monomer represented by Chemical Formula 1, as an example, may be included in an amount of 15 to 30 parts by weight, more preferably 15 to 20 parts by weight, per 100 parts by weight of the acrylic copolymer described above. If the polyfunctional monomer is contained in an amount of less than 15 parts by weight, it may not be sufficient to exhibit a synergistic effect in preventing moisture penetration and durability, and if it exceeds 30 parts by weight, the crosslinking density becomes excessively high, and there is a risk that durability against impact, etc., may decrease as a result.
[0044] In addition, the glycidyl acrylic monomer may be a compound containing at least one glycidyl group within the monomer, and such known monomers may be used without limitation. As an example, the glycidyl acrylic monomer may be glycidyl (meth)acrylate or methylglycidyl (meth)acrylate, and preferably glycidyl methacrylate. The glycidyl methacrylate may be more advantageous for improving durability through additional curing via the glycidyl group provided within the monomer, as it crosslinks with the aforementioned acrylic copolymer and polyfunctional monomer through the acryloyl group.
[0045] The above glycidyl acrylic monomer may be included in an amount of 25 to 40 parts by weight, more preferably 25 to 30 parts by weight, per 100 parts by weight of acrylic copolymer. If the glycidyl acrylic monomer is contained in an amount of less than 25 parts by weight, the formation of a cured body using glycidyl groups may be insufficient, and the improvement in durability may be minimal. If it exceeds 40 parts by weight, the crosslinking density becomes excessively high, and as the hardness of the cured body increases, there is a risk that durability against impact, etc., may decrease.
[0046] In addition, if the acrylic mixed resin content in the one-component composition is less than 35% by weight, there may be a problem with poor mechanical properties of the grout material, and if it exceeds 48% by weight, there may be a problem with poor properties such as waterproofing of the grout material due to a relative lack of other components, so it is appropriate to use it within the above range.
[0048] Next, among the components of the first composition, the bonding promoter plays a role in improving mechanical properties by increasing the bonding strength between the back-surface waterproofing liquid components and increasing adhesion to concrete structures, and includes a phosphate-based compound and a compound represented by the following chemical formula 2, preferably including the phosphate-based compound and the compound represented by the following chemical formula 2 in a weight ratio of 1:1.5 to 3.0, and more preferably including the phosphate-based compound and the compound represented by the following chemical formula 2 in a weight ratio of 1:1.8 to 2.4.
[0049] The above phosphate-based compound may include one or more selected from hydroxyethyl acryloyl phosphate and hydroxyethyl methacrylate phosphate.
[0050] [Chemical Formula 2]
[0051] (R-CHOCH2CH2) n Si(CH2CH2CH2SO3H) m
[0052] In Chemical Formula 2, R is C2 to C containing one or more double bonds. 10 straight-chain alkenyl groups or C3~C 10 It is a fragmented alkenyl group, preferably a straight-chain alkenyl group of C3 to C8 containing one or more double bonds, and more preferably a straight-chain alkenyl group of C3 to C5 containing one or more double bonds. And, n is an integer from 1 to 2, m is an integer from 2 to 3, and n+m is 4.
[0053] In addition, if the content of the bonding promoter is less than 4.0% by weight of the total weight of the one-component mixture, the bonding strength retention of the grout material at high temperatures resulting from its use may be poor, and if it exceeds 8.0% by weight, it may increase the viscosity of the one-component mixture too much, thereby reducing workability, so it is recommended to use it within the above range.
[0055] In addition, among the components of the first-component formulation, the above-mentioned property enhancer plays a role in increasing the weather resistance of the backwater barrier liquid against temperature changes, and a compound represented by the following chemical formula 3 may be used. Furthermore, if the content of the property enhancer is less than 1.0 weight% of the total weight% of the first-component formulation, the effect of improving physical properties due to its use may be insufficient, and if it exceeds 3.0 weight%, excessive use may actually reduce the waterproofing of the backwater barrier liquid, so it is preferable to use it within the above range.
[0056] [Chemical Formula 3]
[0057]
[0058] In Chemical Formula 3, R 1 is a hydrogen atom or a straight-chain alkyl group having 1 to 3 carbon atoms, preferably a methyl group or an ethyl group. The above R of Formula 3 2 is a straight-chain alkyl group having 1 to 5 carbon atoms or a branched-chain alkyl group having 3 to 5 carbon atoms, preferably a straight-chain alkyl group having 1 to 3 carbon atoms. In addition, the above R of Formula 3 3 silver and R4 is a straight-chain alkylene group having 2 to 5 carbon atoms or a branched-chain alkylene group having 3 to 5 carbon atoms, preferably an ethylene group or a propylene group. And, the above R 5 is a straight-chain alkylene group having 2 to 5 carbon atoms, preferably a propyl group or an n-butylene group. Also, B in Formula 2 represents a terminal blocking group, and n is a number satisfying a weight-average molecular weight of 3,000 to 10,000 of the compound, preferably a number satisfying a weight-average molecular weight of 5,000 to 8,000.
[0060] In addition, among the components of the first-component formulation, the powdered silicone water repellent plays a role in improving the water repellency of the backwater barrier and reducing the moisture absorption rate, and thereby serves as a component that improves constructability and workability; as for the powdered silicone water repellent, n-(C6~C 20 alkyl)trialkoxysilane, preferably n-(C6~C 14 alkyl)trialkoxysilane, more preferably n-(C8~C 14 alkyl)trimethoxysilanes and n-(C8~C 14 It may include one or more selected from alkyl)triethoxysilanes. Also, if the content of the powdered silicone water repellent is less than 1.0 weight% of 100 weight% of the one-component composition, the amount used is too small and the effect of improving water repellency due to its use may be insufficient, and if it is used in excess of 4.0 weight%, it may actually reduce the durability of the back-surface waterproofing liquid, so it is appropriate to use it within the above range.
[0062] In addition, among the components of the first-component formulation, the shrinkage inhibitor is used to prevent shrinkage during the curing process after the back-surface waterproofing liquid is injected into the cracks. A general shrinkage inhibitor used in the industry may be used, and preferably, it may include one or more types consisting of styrene-based copolymer, polyethylene, poly(ethylene-propylene) copolymer, PVC, PVA, PMMA, polycaprolactone, styrene-butadiene rubber, chloroprene rubber, and modified polyurethane, and more preferably, it may be a poly(ethylene-propylene) copolymer. More preferably, the poly(ethylene-propylene) copolymer may be one in which ethylene and propylene are copolymerized in a weight ratio of 1:0.2 to 0.3 and has a weight-average molecular weight of 2,300 to 5,000, which is very advantageous for preventing shrinkage that occurs when the aforementioned acrylic resin mixture is crosslinked. If the copolymerization ratio of ethylene and propylene deviates from the aforementioned range, it may be difficult to fully exhibit shrinkage prevention performance, or it may instead impair durability or impair the filling ability of the back-wall liquid.
[0063] In addition, if the above shrinkage inhibitor is less than 0.7 weight% of the one-component mixture, the shrinkage prevention effect may be insufficient when curing the acrylic resin mixture of the present invention, and if used in excess of 1.7 weight%, it may hinder the filling ability of the back-wall opaque liquid, so it is appropriate to use it within the above range.
[0064] In addition, among the components of the first solution, the above-mentioned defoamer plays a role in improving strength and appearance by preventing the formation of large pores in the back-wall waterproofing liquid, and comprises fatty acid-based defoamers such as oleic acid, stearic acid and their alkylene oxide adducts; fatty acid ester-based defoamers such as glycerin monoricinoleate, alkenylsuccinic acid fluid, sorbitol monolaulate, sorbitol trioleate, natural wax, etc.; and oxyalkylene-based defoamers such as polyoxyalkylenes, (poly)oxyalkyl ethers, acetylene ethers, (poly)oxyalkylene fatty acid esters, (poly)oxyalkylene sorbitan fatty acid esters, (poly)oxyalkylene alkyl(aryl)ether sulfate salts, (poly)oxyalkylene alkyl phosphate esters, (poly)oxyalkylene alkylamines, (poly)oxyalkyleneamides, etc. One or more selected from alcohol-based defoaming agents such as octyl alcohol, hexadecyl alcohol, acetylene alcohol, glycols, etc.; phosphate ester-based defoaming agents such as tributyl phosphate, sodium octyl phosphate, etc.; and silicone-based defoaming agents such as dimethyl silicone oil, silicone paste, silicone emulsion, polyorganosiloxane such as dimethylpolysiloxane, fluorosilicone oil, etc. may be used. In addition, if the content of the defoaming agent is less than 0.1% by weight of 100% by weight of the one-component composition, the effect of removing generated bubbles is insufficient and may weaken the strength, and if it is used in excess of 1.0% by weight, it is considered an overuse and may actually reduce water resistance, so it is preferable to use it within the above range.
[0066] In addition, among the components of the first composition, the inorganic binder may comprise 10 to 20 parts by weight of gypsum and 20 to 30 parts by weight of calcium sulfoaluminate per 100 parts by weight of mixed cement comprising ordinary Portland cement and alumina cement in a weight ratio of 1:0.4 to 0.6, and preferably may comprise 12 to 18 parts by weight of gypsum and 20 to 25 parts by weight of calcium sulfoaluminate per 100 parts by weight of mixed cement comprising ordinary Portland cement and alumina cement in a weight ratio of 1:0.45 to 0.50.
[0068] Next, the two-component component, which is the curing agent component among the components of the two-component acrylic waterproofing grout material, comprises a polymerization initiator and water for polymerizing an acrylic resin mixture, preferably comprising a persulfate compound as the polymerization initiator, and may further comprise a reducing agent, an amine compound, an emulsifier, a stabilizer, and a solvent. Additionally, as an example, it may comprise 35 to 45 weight% of a polymerization initiator and the remainder of water based on the total weight of the second component, or it may comprise 35 to 45 weight% of a polymerization initiator, 3 to 10 weight% of a reducing agent, 2 to 5 weight% of an amine compound, 2 to 6 weight% of an emulsifier, 5 to 10 weight% of a stabilizer, and the remainder of water.
[0069] The polymerization initiator may include a persulfate compound that acts as an oxidation catalyst and may further include a known initiator known to be capable of initiating the polymerization of acrylic monomers. The persulfate compound may include, for example, one or more of sodium persulfate and ammonium persulfate. The polymerization initiator may be contained in an amount of 35 to 45 weight% of the two-component mixture. If the polymerization initiator is less than 35 weight% of the total weight% of the second component, the amount used is insufficient, resulting in a curing speed that is too slow and, after curing, low mechanical strength; if it exceeds 45 weight%, the curing speed after mixing with the first component is excessive, which may lead to reduced workability.
[0070] In addition, among the components of the two-component mixture, the reducing agent is a substance that facilitates the generation of radicals for polymerization by decomposing the polymerization initiator, and may be used without limitation if it is a known substance known to help decompose the polymerization initiator. For example, the reducing agent may include one or more of sodium bisulfite, sodium metabisulfite, sodium hydrosulfite, sodium thiolsulfite, sodium formaldehyde sulfoxylate, etc. The reducing agent may be contained in the second agent at a concentration of 3 to 10 weight percent; if contained at less than 3 weight percent, it may be difficult to achieve sufficient curing density, and if contained at more than 10 weight percent, the curing speed may be excessive, potentially leading to reduced workability.
[0071] In addition, among the components of the two-component formulation, the amine-based compound is a curing agent involved in the curing of glycidyl groups within the glycidyl acrylic monomer contained in the acrylic resin mixture. It may be used without limitation as a known amine-based curing agent used for the curing of glycidyl groups, and may include, for example, one or more of triethylamine, methylenedianylene, triethanolamine, isophorone diamine, and diethanolamine. More preferably, the amine-based compound may include triethylamine and methylenedianylene, and even more preferably, triethylamine and methylenedianylene may be included in a weight ratio of 1:0.15 to 0.2, which may be more advantageous for achieving the objectives of the invention, such as further improving the waterproofing performance. If methylenedianylene is contained in an amount less than 0.15 times that of triethylamine, the synergistic effect of waterproofing performance may be negligible, and if methylenedianylene is contained in an amount exceeding 0.2 times, there is a concern that durability may be reduced due to external forces such as vibration, which may be disadvantageous to achieving the purpose of the present invention. The above amine-based compound may be contained in 2 to 5 weight percent of the second agent, and if it is less than 2 weight percent, the effect of improving physical properties due to heterocrosslinking using glycidyl, in addition to crosslinking between acrylic compounds through glycidyl-containing acrylic monomers, may be negligible, and if it exceeds 5 weight percent, the effect on curing may be negligible and material costs may increase.
[0073] In addition, among the components of the two-component formulation, the emulsifier may be a known emulsifier used in the polymerization of acrylic compounds, and may include, for example, one or more of anionic surfactants such as fatty acids, sulfates, and sulfonates; nonionic surfactants such as polyethylene oxide, alkyl iders, alkylaryl iders, alkylamines, polyol esters, and glycerin; cationic surfactants such as amines and quaternary ammoniums; and amphoteric surfactants such as carboxylates, aminocarboxylates, and betaines. Preferably, the emulsifier may include polyoxyethylene lauryl ether and polyether-modified polysiloxane, and more preferably, polyoxyethylene lauryl ether and polyether-modified polysiloxane may be included in a weight ratio of 1:0.3 to 0.5, thereby uniformly dispersing the components of the first and second components and performing the role of stabilizing them so that they do not re-aggregate before solidification. The above emulsifier may be contained in an amount of 2 to 6 weight percent in the two-component mixture. If the amount is less than 2 weight percent, the amount is too small, so the dispersibility and anti-aggregation effects resulting from its use may be insufficient. If the amount exceeds 6 weight percent, it may actually reduce the adhesion and bonding strength of the back-surface waterproofing liquid to concrete structures, etc. Therefore, it is appropriate to use it within the above range.
[0074] In addition, among the components of the two-component formulation, the stabilizer plays a role in improving and maintaining the stability of the cured structure after curing, and may include, for example, a phosphate. It plays a role in improving and maintaining the stability of the cross-linked structure after the formation of the cross-linked structure, and may be contained in the second component at 5 to 10 weight percent. If the phosphate is less than 5 weight percent or exceeds 10 weight percent of the total weight percent of the second component, the stabilization effect decreases, so it is appropriate to use it within the above range.
[0075] The two-component acrylic waterproofing grout material composed of the aforementioned first and second components can form a backwater waterproofing liquid either on its own or mixed with a suitable solvent to adjust viscosity, and can repair cracked areas by mixing and stirring before construction and then injecting it under high pressure through an injection hole. At this time, the solvent may be water or a known organic solvent used in acrylic waterproofing compositions, and the present invention is not specifically limited thereto. In addition, the injection of the backwater waterproofing liquid may be carried out by varying the injection amount and range according to the injection pressure and the state of leakage, and the present invention is not specifically limited thereto.
[0076] In addition, the mixing ratio of the first component and the second component may be 1:0.10 to 0.40 by weight, preferably 1:0.10 to 0.30 by weight, but is not limited thereto.
[0077] In addition, water can be mixed to increase viscosity, and the mixing ratio of the liquid component and water can be 1:0.20 to 0.50 by weight, preferably 1:0.20 to 0.40 by weight.
[0078] The two-component acrylic waterproof grout material of the present invention, manufactured with this composition, has good ultra-low viscosity retention properties that maintain low viscosity until just before gelation to maximize injection efficiency and facilitate long-distance penetration, and even with repeated drying shrinkage, there is almost no change in physical properties in terms of performance, and due to its non-shrinkage properties, it has the performance effect of a high-strength, high-elasticity injection material with high tensile strength and elongation.
[0080] Next, the guided waterproofing method of the inner surface waterproof acrylic-based back grouting composite reinforcement method of the present invention is described as follows.
[0081] The above-mentioned induction waterproofing method performs a process comprising: Step 2-1, preparing the construction surface of the joint; Step 2-2, applying an EVA (ethylene vinyl acetate)-based coating material to the prepared construction surface; Step 2-3, attaching a grid fiber reinforcement sheet to the construction surface coated with the EVA-based coating material; and Step 2-4, applying an EVA-based coating material to the grid fiber reinforcement sheet to form a finishing layer.
[0082] The joints in step 2-1 may be joints of induction waterproofing boards, inter-layer joints, sash joints, and / or structural joints.
[0084] For the EVA-based coating materials in steps 2-2 and 2-4, the same or different EVA-based coating materials may be used, and preferably, using the same ones is advantageous in terms of ease of construction and unit cost.
[0085] The above EVA-based coating material may use a general primer used in waterproofing construction in the industry, but preferably, an EVA-based coating material comprising ethylene vinyl acetate resin, ethylene vinyl acetate modified polymer resin, trialkoxysilane monomer, PVA (polyvinyl) fiber, dispersant, and solvent may be used.
[0086] These EVA-based coating agents have excellent adhesion as film waterproofing materials, good compatibility with inorganic components, and offer superior resistance to neutralization, corrosion, surface strength reinforcement, and moisture penetration. Furthermore, they exhibit good resistance to shrinkage and expansion, providing excellent protection against cracks caused by moisture penetration.
[0087] And, the EVA-based coating material may comprise 40.0 to 50.0 wt% ethylene vinyl acetate resin, 10.0 to 15.0 wt% ethylene vinyl acetate modified polymer resin, 3.0 to 8.0 wt% trialkoxysilane monomer, 0.1 to 1.2 wt% PVA (polyvinyl) fiber, 2.0 to 4.0 wt% dispersant, and the remaining amount of solvent among 100 wt%, and preferably 42.0 to 48.0 wt% ethylene vinyl acetate resin, 12.0 to 15.0 wt% ethylene vinyl acetate modified polymer resin, 4.0 to 7.0 wt% trialkoxysilane monomer, 0.1 to 1.0 wt% PVA (polyvinyl) fiber, 2.0 to 3.5 wt% dispersant, and the remaining amount among 100 wt% It may include a solvent, and more preferably, may include 44.0 to 48.0 wt% of ethylene vinyl acetate resin, 12.0 to 14.0 wt% of ethylene vinyl acetate modified polymer resin, 4.0 to 6.0 wt% of trialkoxysilane monomer, 0.2 to 0.6 wt% of PVA (polyvinyl) fiber, 2.5 to 3.5 wt% of dispersant, and the remaining amount of solvent among 100 wt%.
[0088] If the content of ethylene vinyl acetate resin in the above EVA-based coating material composition is less than 40.0 weight%, there may be a problem with insufficient bonding strength with the substrate surface, the bonding strength with the grid fiber reinforcing sheet, and the adhesion retention strength, and if more than 50.0 weight% is used, the spreadability of the coating material decreases, and there may be a problem with poor workability.
[0089] In addition, the ethylene vinyl acetate modified resin among the components of the EVA-based coating material is an ethylene vinyl acetate graft polymer prepared by adding a reaction initiator to a mixture of 40 to 60 parts by weight of methyl methacrylate and 800 to 1,000 parts by weight of methyl ethyl ketone, with respect to 100 parts by weight of ethylene vinyl acetate resin having a degree of chloride of 10.0 to 20.0 wt%, and the ethylene vinyl acetate modified resin plays a role in increasing the waterproofness and crack resistance of the undercoat layer. In addition, if its content is less than 10 wt% of the total weight of the EVA-based coating material, the effect of its use may be insufficient, and if it is used in excess of 15.0 wt%, there may be a problem of reduced miscibility between the components of the EVA-based coating material.
[0090] In addition, among the components of the EVA-based coating material, the trialkoxysilane monomer plays a role in increasing adhesion with the substrate and increasing bonding strength with the grid fiber reinforcing sheet, and 3-trialkoxysilylalkyl methacrylate or trialkoxy vinylsilane may be used, preferably 3-trialkoxysilylalkyl methacrylate may be used, and more preferably, one or more selected from 3-trimethoxysilylpropyl methacrylate, 3-triethoxysilylpropyl methacrylate, 3-tripropoxysilylpropyl methacrylate, 3-trimethoxysilylbutyl methacrylate, 3-triethoxysilylbutyl methacrylate and 3-tripropoxysilylbutyl methacrylate may be included. In addition, if the content is less than 3.0 weight% of the total weight of the EVA-based coating material, the effect of using it may be insufficient, and if it is used in excess of 8.0 weight%, there may be a problem where the spreadability and coating properties of the EVA-based coating material are significantly reduced.
[0091] In addition, PVA (polyvinyl) fibers among the components of EVA-based coating materials play a role in increasing the durability and crack prevention of the undercoat layer. If the content is less than 0.1% by weight of the total weight of the EVA-based coating material, the effect of using it may be insufficient, and if it is used in excess of 1.0% by weight, it may clump within the EVA-based coating material and actually reduce durability, so it is recommended to use it within the above range.
[0092] In addition, the above-mentioned dispersant serves to increase the miscibility of EVA-based coating material components and the dispersibility of PVA fibers, and may include one or more selected from unsaturated polycarboxylic acid polymer-based dispersants, unsaturated polyamine amide salt-based dispersants, and polymer block copolymer solution-based dispersants. Furthermore, if the content is less than 2.0% by weight of the total weight of the EVA-based coating material, the effect of its use may be negligible, and if it exceeds 4.0% by weight, it is an excessive use, which may lead to a deterioration in the physical properties of the undercoat layer; therefore, it is preferable to use it within the above range.
[0093] The above solvent may be water or an aqueous alcohol solution, preferably water, and the solvent content is the remainder of 100% by weight in addition to the EVA-based coating material components described above.
[0094] In addition, it is appropriate to apply the EVA-based coating material to the application surface at a rate of 0.05 to 0.20 kg / m², preferably 0.05 to 0.15 kg / m².
[0096] Next, the 2-3 stage attachment construction can be performed by using grid fiber reinforcement sheets to reinforce the joints.
[0097] The grid fiber reinforcement sheet used in the above-mentioned attachment construction is a fiber sheet that has been needle-punched and grid-punched, and is a fiber sheet in which multiple fine holes formed by needle punching and multiple cross-shaped holes formed by grid punching are arranged regularly or irregularly. Such a grid fiber reinforcement sheet has excellent behavioral performance due to shrinkage and expansion, good waterproofing properties, and excellent impregnation properties for EVA-based coating materials used to form the undercoat layer by grid punching.
[0098] In addition, the grid fiber reinforcing sheet is a composite sheet in which polymer nanofiber layers are laminated on both sides of a thermoplastic elastomer sheet layer, and the thermoplastic elastomer sheet layer has a thickness of 0.1 to 1.0 mm, preferably 0.2 to 0.8 mm, and more preferably 0.2 to 0.6 mm. In addition, each of the polymer nanofiber layers on both sides of the thermoplastic elastomer sheet layer may have a thickness of 0.1 to 2.0 mm, preferably 0.2 to 1.5 mm, and more preferably 0.4 to 1.0 mm.
[0099] The thermoplastic elastomer sheet layer of the grid fiber reinforcement sheet can be manufactured from a composition comprising a thermoplastic elastic resin, a waterproofing promoter, a moisture absorbent, a plasticizer, an inorganic filler, a dispersant, and additives.
[0100] The thermoplastic elastic resin in the above composition is a reaction product obtained by reacting a reaction product comprising a condensation polymer obtained by polymerizing a soft segment component and the remainder of a hard segment component; and 5-Na sulfoisophthalic acid dihydroxyethyl ester. The 5-Na sulfoisophthalic acid dihydroxyethyl ester plays a role in significantly increasing the flexibility (or bendability) of the thermoplastic elastomer sheet made of the thermoplastic elastic resin, and preferably, the content of 5-Na sulfoisophthalic acid dihydroxyethyl ester in the reaction product is 0.7 to 2.0 weight%, preferably 1.0 to 2.0 weight%, and more preferably 1.2 to 1.8 weight%. At this time, if the content in the reactant is less than 0.7 weight%, the effect of increasing flexibility (or bendability) due to its application may be insufficient, and if it exceeds 2.0 weight%, the elasticity and resilience of the thermoplastic elastomer sheet may actually decrease significantly, so it is preferable to use it within the above range. Also, the content of the condensation polymer in the reactant is the remainder excluding 5-Na sulfoisophthalic acid dihydroxyethyl ester.
[0101] In addition, the above condensation polymer is a condensation polymer obtained by polymerizing 30 to 50 weight% of a soft segment component and the remainder of a hard segment component, preferably a condensation polymer obtained by polymerizing 36 to 45 weight% of a soft segment component and the remainder of a hard segment component, and more preferably a condensation polymer obtained by polymerizing 38 to 44 weight% of a soft segment component and the remainder of a hard segment component. At this time, if the soft segment component content is less than 30 weight%, the elasticity and resilience of the thermoplastic elastomer sheet may decrease and long-term waterproofing performance may decrease, and if it exceeds 50 weight%, although the flexibility of the thermoplastic elastomer sheet is high, there may be a problem of relatively low mechanical strength, so it is preferable to include the soft segment component within the above range.
[0102] And, the soft segment component may include three types of polyols as polyol components, namely polyethylene glycol, poly(tetramethylene) glycol, and polypropylene glycol, preferably in a weight ratio of 1:0.3 to 0.5:0.05 to 0.10, and more preferably in a weight ratio of 1:0.35 to 0.47:0.05 to 0.08.
[0103] The hard segment component may include polybutylene terephthalate and polyethylene terephthalate, preferably in a weight ratio of 1:0.1 to 0.3, and more preferably in a weight ratio of 1:0.15 to 0.20.
[0104] Among the above compositions, the waterproofing promoter comprises ethylene vinyl acetate resin and amorphous poly-alpha-olefin resin, preferably comprising ethylene vinyl acetate resin and amorphous poly-alpha-olefin resin in a weight ratio of 1:0.1 to 0.3, and more preferably comprising ethylene vinyl acetate resin and amorphous poly-alpha-olefin resin in a weight ratio of 1:0.14 to 0.20, in terms of improving waterproofing and compatibility with other compositions.
[0105] In addition, the above ethylene vinyl acetate resin may be used as a resin having an ethylene content of 25 to 35 weight% and a weight-average molecular weight of 5,000 to 15,000, preferably having an ethylene content of 27 to 35 weight% and a weight-average molecular weight of 7,000 to 12,000.
[0106] In addition, the above-mentioned amorphous poly-alpha-olefin resin serves to enhance the waterproofing effect of the waterproofing promoter and may include one or more selected from poly(ethylene-co-propylene) resin, poly(ethylene-co-butylene) resin, poly(propylene-co-butylene) resin, and ethylene methyl methacrylate copolymer resin, and preferably may include one or more selected from poly(ethylene-co-propylene) resin and poly(ethylene-co-butylene) resin.
[0107] Among the above compositions, the moisture absorbent acts to increase the waterproofness of the waterproof sheet by absorbing moisture, such as moisture introduced from the outside, and includes one or more selected from polyacrylamid, methacrylic acid, and polyethylene glycol, and preferably may include one or more selected from methacrylic acid and ethylene glycol.
[0108] The dispersant in the above composition plays a role in increasing the miscibility between compositions used in the manufacture of thermoplastic elastic resins to provide uniformity in thermal insulation and waterproofing effects, and may include a polymer obtained by polymerizing a 2-oxazoline polymer and an acrylic acid monomer, and preferably may include a polymer obtained by polymerizing a 2-oxazoline polymer and an acrylic acid monomer in a molar ratio of 1:0.3 to 0.4.
[0109] The plasticizer in the above composition may include one or more selected from diisononyl adipate, dioctyl adipate, dioctyl terephthalate, and tributyl citrate, preferably may include one or more selected from diisononyl adipate, dioctyl adipate, and tributyl citrate, and more preferably may be used by mixing diisononyl adipate and tributyl citrate in a weight ratio of 1:0.5 to 1.0.
[0110] Among the above compositions, the inorganic filler is a powder-type inorganic filler and may include one or more selected from calcium carbonate, talc, titanium dioxide, kaolin, silica, alumina, and magnesium hydroxide, and preferably may include one or more selected from titanium dioxide, kaolin, silica, alumina, and magnesium hydroxide.
[0111] The additives in the above composition are compositions intended to provide additional functions and effects to thermoplastic elastomer sheets, and may include general antioxidants, heat stabilizers, flame retardants, dyes, pigments, antibacterial agents, light stabilizers, adhesion promoters, antistatic agents, lubricants, interblocking agents, etc. used in the industry, and general materials used in the industry may be used as additive components.
[0112] For example, the above antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide), 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphoate, ,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, Examples include 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, etc.
[0113] The above heat stabilizer is used to improve weather resistance, heat resistance and durability, and benzotriazole, phenol antioxidants, alkylated monophenol, alkylthiomethylphenol, hydroquinone, alkylated hydroquinone, hydroxybenzyl, triazine, etc. may be used without limitation.
[0114] The above flame retardant may be an organic or inorganic phosphorus compound. Examples of such organic or inorganic phosphorus compounds include oxo acids of phosphorus such as phosphoric acid, phosphonic acid, phosphinic acid, phosphinic acid, and polyphosphoric acid; metal salts of acidic pyrophosphates such as sodium acidic pyrophosphate, potassium acidic pyrophosphate, and calcium acidic pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, organic phosphonite compounds, etc., and organic phosphite compounds are particularly preferred. Examples of organic phosphite compounds include triphenylphosphite, tris(monononylphenyl)phosphite, tris(monononyl / dinonyl-phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyldiphenylphosphite, dioctylmonophenylphosphite, monodecyldiphenylphosphite, didecylmonophenylphosphite, tridecylphosphite, trilaurylphosphite, tristearylphosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite.
[0115] Examples of the above dyes and / or pigments include inorganic pigments, organic pigments, organic dyes, etc. Specifically, sulfide-based pigments such as cadmium red and cadmium yellow; phthalocyanine-based dye pigments such as copper phthalocyanine blue and copper phthalocyanine green; azo-based dye pigments such as nickel azo yellow; etc. are preferred.
[0116] The above antimicrobial agent may be an organic antimicrobial agent and / or an inorganic antimicrobial agent, and as an example, an inorganic antimicrobial agent such as zinc, silver, copper, titanium and their oxides may be used.
[0117] And, the composition used for manufacturing the thermoplastic elastomer sheet may comprise, excluding the solvent, an amount of the components in the composition of 8.0 to 12.0 wt% of the waterproofing promoter, 2.0 to 5.0 wt% of the moisture absorbent, 0.5 to 2.0 wt% of the plasticizer, 1.0 to 5.0 wt% of the inorganic filler, 0.5 to 1.0 wt% of the dispersant, 1.0 to 5.0 wt% of the additive, and the remainder of the thermoplastic elastomer resin, and preferably comprises 10.0 to 12.0 wt% of the waterproofing promoter, 2.5 to 4.5 wt% of the moisture absorbent, 0.6 to 1.7 wt% of the plasticizer, 3.0 to 4.0 wt% of the inorganic filler, 0.5 to 0.8 wt% of the dispersant, 2.0 to 5.0 wt% of the additive, and the remainder of the thermoplastic elastomer resin. Including it is advantageous in terms of securing water resistance, shape retention, resilience, elasticity, and appropriate flexibility through the thermoplastic elastomer sheet.
[0119] The polymer nanofiber layer, which is integrated by laminating and bonding the above grid fiber reinforcement sheet to both sides of the thermoplastic elastomer sheet, serves to provide adhesion between the substrate and the thermoplastic elastomer sheet and to protect against surface impact, or to form a composite waterproof structural layer by combining the hard coat liquid and the fiber sheet when a primer is applied. The polymer nanofiber layer may be formed by adhering a nonwoven fabric or sheet made of polymer nanofibers to both sides of the thermoplastic elastomer sheet; preferably, forming it by electrospinning on both sides of the waterproof sheet is advantageous in terms of reducing the use of non-environmentally friendly adhesives.
[0120] A polymer nanofiber layer can be formed by electrospinning a polymer spinning solution onto one or both sides of a thermoplastic elastomer sheet using the thermoplastic elastomer sheet as a substrate. The polymer spinning solution is a solution in which a polymer resin is dissolved in an organic solvent, and can be prepared using various polymers and various organic solvents. The polymer resin used at this time may be a thermoplastic polymer comprising one or more selected from polyimide, polyethylene terephthalate, nylon, polyaramid, polybenzimidazole, polyetherimide, polyacrylonitrile, polyaniline, polyethylene oxide, PN (polyethylene naphthalate), polystyrene, PVC (polyvinyl chloride), polyvinyl alcohol, polyvinylidene fluoride, polyvinyl butylene, poly L-lactic acid, and propylene glycol alginate that can be dissolved in an organic solvent, preferably a thermoplastic polymer comprising one or more selected from polyvinyl alcohol, polyvinylidene fluoride, polyvinyl butylene, and propylene glycol alginate, and more preferably, polyvinyl alcohol, polyvinylidene fluoride, and polyvinyl butylene may be mixed in a weight ratio of 1:0.1 to 0.2:0.2 to 0.3.
[0121] In addition, the organic solvent, which is a component of the polymer spinning solution, is preferably one or more selected from propylene carbonate, butylene carbonate, 1,4-butyrolactone, diethyl carbonate, dimethyl carbonate, 1,2-dimethoxyethane, 1,3-dimethyl-2-imidazolidinone, dimethyl sulfoxide, ethylene carbonate, ethylmethyl carbonate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, polyethylenesulfolane, tetraethylene glycol dimethyl ether, acetone, alcohol, or a mixture thereof, and it is more preferable to use one or more selected from dimethyl sulfoxide, ethylene carbonate, ethylmethyl carbonate, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.
[0122] In addition, the polymer spinning solution may also optionally include a combination of additives such as reactive adhesives, water repellents, hydrophilic agents, and flame retardants.
[0123] In addition, the polymer nanofiber layer has an average nanofiber diameter of 200 to 500 nm and a bonding amount of the polymer nanofiber layer to the thermoplastic elastomer sheet layer of about 0.30 to 0.70 g / m², preferably an average nanofiber diameter of 250 to 320 nm and a bonding amount of about 0.40 to 0.60 g / m², and more preferably an average nanofiber diameter of 280 to 320 nm and a bonding amount of about 0.40 to 0.55 g / m², which is suitable in terms of durability.
[0125] Next, the EVA-based coating material of step 2-4 can be the same as the EVA-based coating material of step 2-2, and the amount of EVA-based coating material applied in step 2-4 is 0.15 to 0.30 kg / m², preferably 0.15 to 0.25 kg / m², so that the grid fiber reinforcing sheet is completely impregnated.
[0127] The present invention will be explained in more detail below through examples, but the following examples are not intended to limit the scope of the invention and should be interpreted as being for the purpose of aiding understanding of the invention.
[0128] [Example]
[0129] Preparation Example 1: Preparation of EVA-based coating material
[0130] (1) Preparation of ethylene vinyl acetate modified resin
[0131] In a 500 ml reactor equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen injection device in a mixing vessel, 980 parts by weight of MEK (methyl ethyl ketone) as a solvent was added to 48 parts by weight of methyl methacrylate to 100 parts by weight of ethylene vinyl acetate resin (Superchlon BAS0, NIPPON PAPER CHEMICALS) with a chloride degree of 14.8 wt%, and then slowly stirred at 70°C for 1 hour.
[0132] Next, benzoyl peroxide was added, and the temperature was raised to 80°C while maintaining the stirring speed to perform a graft reaction, thereby producing a graft polymer, ethylene vinyl acetate modified resin.
[0133] (2) Manufacture of EVA-based coating materials
[0134] An EVA-based coating material was prepared by mixing and stirring 46.2 wt% of ethylene vinyl acetate resin, 12.7 wt% of ethylene vinyl acetate modified polymer resin, 4.4 wt% of trialkoxysilane monomer, 0.33 wt% of PVA (polyvinyl) fiber, 2.8 wt% of dispersant, and the remaining amount of solvent out of 100 wt%.
[0136] Preparation Example 2-1: Preparation of a thermoplastic elastomer sheet
[0137] A polycondensation reaction was performed in a polycondensation reactor with 41.2 wt% of a soft segment component, which is a polyol containing polyethylene glycol, poly(tetramethylene) glycol, and polypropylene glycol in a weight ratio of 1:0.42:0.07, and 58.8 wt% of a hard segment component containing polybutylene terephthalate and polyethylene terephthalate in a weight ratio of 1:0.16, while increasing the temperature to 255°C for 120 minutes (reducing the reaction pressure from 760 torr to 0.3 torr for 60 minutes, and then maintaining a high vacuum of 0.3 torr or less for 60 minutes), after which the reaction product was discharged out of the reactor and cooled to produce a polycondensation polymer.
[0138] Next, a thermoplastic elastic resin was prepared by reacting a reaction mixture containing 1.47 wt% of 5-Na sulfoisophthalic acid dihydroxyethyl ester and the remainder of the condensation polymer.
[0139] Separately, a waterproofing promoter was prepared containing ethylene vinyl acetate resin (ethylene content 28-32 wt%, Mw 7,500-9,000) and poly(ethylene-co-butylene) resin in a weight ratio of 1:0.15.
[0140] In addition, mechacryl acid was prepared as a moisture absorbent.
[0141] In addition, a polymer obtained by polymerizing 2-oxazoline polymer and acrylic acid monomer in a molar ratio of 1:0.36 was prepared as a dispersant.
[0142] In addition, a plasticizer was prepared by mixing diisononyl adipate and tributyl citrate in a weight ratio of 1:0.64.
[0143] As a powdered inorganic filler, a 1:1 mixture of kaolin powder and alumina powder was prepared.
[0144] As additives, hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, hydroxybenzyl as a heat stabilizer, 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite as a flame retardant, and copper oxide powder as an antimicrobial agent were prepared.
[0145] Next, a composition comprising 11.5 wt% of the thermoplastic elastic resin, 2.8 wt% of the water-repellent promoter, 0.9 wt% of the plasticizer, 3.5 wt% of the inorganic filler, 0.7 wt% of the dispersant, 0.7 wt% of the antioxidant, 0.8 wt% of the heat stabilizer, 1.2 wt% of the flame retardant, 0.3 wt% of the antibacterial agent, and the remainder of 100 wt% of the thermoplastic elastic resin was mixed and stirred with a mixed solvent containing 1-methoxy-2-propanol and diethylene glycol modoethyl ether acetate in a 1:1 volume ratio to produce a sheet-forming resin, and then the sheet-forming resin was coated onto a release layer and heat-treated to produce a thermoplastic elastomer sheet with a thickness of 0.5 mm.
[0147] Preparation Examples 2-2 to 2-3 and Comparative Preparation Example 2-1
[0148] Thermoplastic elastomer sheets were prepared in the same manner as in Preparation Example 2-1 above, but with different amounts of the sheet-forming resin composition as shown in Table 1 below, and Preparation Examples 2-2 to 2-3 and Comparative Preparation Example 2-1 were carried out respectively.
[0150] Comparative Preparation Example 2-2
[0151] A sheet was prepared in the same manner as in Preparation Example 2-1 above, but a thermoplastic elastic resin was prepared using a condensation polymer in which 28% by weight of the soft segment component and the remainder of the hard segment component were polymerized.
[0153] Comparative Preparation Example 2-3
[0154] A thermoplastic elastomer sheet was prepared using a thermoplastic elastic resin prepared by polymerizing a condensation polymer with 52% by weight of the soft segment component and the remainder of the hard segment component, in the same manner as in Preparation Example 2-1 above.
[0156] Comparative Preparation Example 2-4
[0157] A sheet was prepared in the same manner as in Preparation Example 2-1 above, but a thermoplastic elastic resin was prepared by reacting a reaction mixture containing 0.4 wt% of 5-Na sulfoisophthalic acid dihydroxyethyl ester and the remainder of the condensation polymer to produce the thermoplastic elastic resin, and a thermoplastic elastomer sheet was prepared using the thermoplastic elastic resin.
[0158] Classification (Weight%) Preparation Example 2-1 Preparation Example 2-2 Preparation Example 2-3 Comparison Preparation Example 2-1 Comparison Preparation Example 2-2 Comparison Preparation Example 2-3 Comparison Preparation Example 2-4 Waterproofing enhancer 11.5 10.0 12.0 11.5 11.5 11.5 11.5 moisture absorbent 2.8 2.2 3.5 2.8 2.8 2.8 2.8 plasticizer 0.9 0.9 1.0 0.9 0.9 0.9 0.9 Weapon filler 3.5 3.5 3.5 3.5 3.5 3.5 3.5 Dispersant 0.7 0.5 0.8 0.2 0.7 0.7 0.7 antioxidants 0.7 0.7 0.7 0.7 0.7 0.7 0.7 Heat stabilizer 0.8 0.8 0.8 0.8 0.8 0.8 0.8 flame retardant 1.2 1.2 1.2 1.2 1.2 1.2 1.2 antibacterial agents 0.3 0.3 0.3 0.3 0.3 0.3 0.3 Thermoplastic elastic resin The remaining amount of 100 weight%
[0160] Experimental Example 1: Measurement of Tensile Strength and Flexural Strength
[0161] The tensile strength of the thermoplastic elastomer sheets prepared in Preparation Examples 2-1 to 2-3 and Comparative Preparation Examples 2-1 to 2-4 was measured according to KSF4917, and the flexibility was measured according to KSF4934 for the formation of cracks (good means no cracks, poor means cracks). The results are shown in Table 2 below.
[0162] division Tensile strength (N / mm) Flexibility Preparation Example 2-1 17.3 Good Preparation Example 2-2 17.7 Good Preparation Example 2-3 16.8 Good Comparative Preparation Example 2-1 14.2 Good Comparative Preparation Example 2-2 19.2 error Comparative Preparation Example 2-3 14.9 Good Comparative Preparation Example 2-4 18.3 error
[0163] Looking at the results of the physical property measurements in Table 2 above, Comparative Preparation Example 2-1, which used less than 0.5 wt% of dispersant, had good flexibility, but compared to Preparation Example 2-2, there was a problem with the tensile strength decreasing rapidly.
[0164] In addition, the thermoplastic elastomer sheet of Comparative Preparation Example 2-2, which was prepared using a thermoplastic elastomer with a condensation polymer having a soft segment component of less than 30 weight%, showed poor flexibility, which is because the elasticity and flexibility of the sheet were reduced.
[0165] In addition, the thermoplastic elastomer sheet of Comparative Preparation Example 2-3, which was prepared using a thermoplastic elastomer with a condensation polymer having more than 50% by weight of soft segment components, had good flexibility but had a problem of significantly lower mechanical strength.
[0166] In addition, the thermoplastic elastomer sheet of Comparative Preparation Example 2-4, which was prepared using a thermoplastic elastomer prepared with less than 1.0 wt% of 5-Na sulfoisophthalic acid dihydroxyethyl ester when preparing the thermoplastic elastomer, showed excellent mechanical strength but poor flexibility.
[0167] In contrast, it was confirmed that each of the thermoplastic elastomer sheets of Preparation Examples 2-1 to 2-3 has excellent mechanical strength with a tensile strength of 16.0 N / mm or more, preferably 16.0 to 18.5 N / mm, and more preferably 16.50 to 18.2 N / mm, while also having excellent flexibility, i.e., bendability.
[0170] Preparation Example 3: Preparation of Grid Fiber Reinforced Sheet
[0171] A polymer spinning solution was prepared by dissolving a mixed resin, in which polyvinyl alcohol, polyvinylidene fluoride, and polyvinyl butylene were mixed in a weight ratio of 1:0.1 to 0.2:0.2 to 0.3, in dimethylformamide (DMF).
[0172] Next, the polymer spinning solution was electrospun as an electrospinning solution on both sides of the thermoplastic elastomer sheet prepared in Preparation Example 2-1 to form a nanofiber layer in which a nanoweb was formed by nanofibers, thereby producing a composite sheet in which a polymer nanofiber layer was formed on both sides of the thermoplastic elastomer sheet. The average diameter of the nanofibers was approximately 292 nm, and the amount of the polymer nanofiber layer attached to the thermoplastic elastomer sheet layer was 0.46 g / m².
[0173] Next, the composite sheet was needle-punched to form a plurality of micro-holes, and then grid-punched to form a plurality of cross-shaped holes, thereby manufacturing a grid fiber reinforced sheet in which micro-holes and cross-shaped holes are regularly arranged.
[0174] The thermoplastic elastomer sheet layer of the grid fiber reinforcement sheet had a thickness of about 0.50 mm, and the polymer nanofiber layers on both sides of the thermoplastic elastomer sheet layer each had a thickness of about 0.85 mm.
[0176] Preparation Example 4-1: Preparation of a two-component acrylic waterproofing grout material
[0177] (1) Preparation of a single-component formulation
[0178] (1-1) Preparation of acrylic mixed resin
[0179] An acrylic resin mixture was prepared by mixing 16 parts by weight of a polyfunctional monomer, which is a compound represented by the following chemical formula 1, and 26 parts by weight of a glycidyl acrylic monomer, which is glycidyl methacrylate, with respect to 100 parts by weight of an acrylic copolymer.
[0180] [Chemical Formula 1]
[0181]
[0182] In Chemical Formula 1, R 1 and R 2 Each is independent and is -CH2CH2CHCH2.
[0183] At this time, the acrylic copolymer was prepared by adding and mixing 1.2 parts by weight of cumene hydroperoxide as an initiator and 8 parts by weight of polyoxyethylene lauryl ether as an emulsifier to 100 parts by weight of a mixed acrylic monomer, in which methyl methacrylate, 3-(trimethoxysilyl)propyl methacrylate, and dicyclopentenyloxyethyl methacrylate were added to a chamber in a molar ratio of 1:0.5:0.9, and then carrying out a polymerization reaction at a polymerization temperature of 80°C for 2.5 hours according to a conventional acrylic emulsion polymerization method to produce an acrylic copolymer having a weight-average molecular weight of about 7200.
[0184] (1-2) Preparation of Solution 1
[0185] 42.0 wt% of the previously manufactured acrylic mixed resin, 5.7 wt% of a binding promoter, A one-component mixture was prepared by mixing 1.6 wt% of a physical property enhancer represented by the following chemical formula 3-2, 1.8 wt% of n-dodecyltriethoxysilane (powdered silicone water repellent), 0.42 wt% of a poly(ethylene-propylene) copolymer (ethylene:propylene in copolymer = 1:0.2 weight ratio, weight-average molecular weight 2520) as a shrinkage inhibitor, 0.3 wt% of glycerin monoricinoleate as an antifoaming agent, and the remaining amount of an inorganic binder out of 100 wt%.
[0186] The above-mentioned bonding promoter was used by mixing hydroxyethyl acryloyl phosphate and a compound represented by the following chemical formula 2-1 in a weight ratio of 1:2.2.
[0187] In addition, the above-mentioned inorganic binder was used by mixing 14 parts by weight of gypsum and 23 parts by weight of calcium sulfoaluminate with 100 parts by weight of mixed cement containing ordinary Portland cement and alumina cement in a weight ratio of 1:0.46.
[0188] [Chemical Formula 2-1]
[0189] (R-CHOCH2CH2) n Si(CH2CH2CH2SO3H) m
[0190] In chemical formula 2-1, R is -CH2CHCHCH2-, n is 2, and m is 2.
[0191] [Chemical Formula 3-1]
[0192]
[0193] In chemical formula 2-1, R 1 is a methyl group, and R 2 is an ethyl group, and R 3 silver and R 4 is an ethylene group, and R 5is a propylene group, B is a tert-butyl group, and n is a number satisfying a polymer weight-average molecular weight of 5,500 to 6,000.
[0194] (2) Preparation of a two-component formulation
[0195] A two-component mixture was prepared by mixing 40% by weight of ammonium persulfate as a polymerization initiator, 7% by weight of sodium thiol sulfite as a reducing agent, 3% by weight of an amine mixture of triethylamine and methylenedianylene in a weight ratio of 1:0.17 as an amine compound, 3% by weight of a mixture of polyoxyethylene lauryl ether and polyether-modified polysiloxane in a weight ratio of 1:0.4 as an emulsifier, 7% by weight of phosphate as a stabilizer, and the remainder being water.
[0197] Comparative Preparation Example 4-1
[0198] A 1-component and a 2-component were prepared in the same manner as in Preparation Example 4-1 above, but the 1-component was prepared without using a binding promoter and a shrinkage inhibitor when preparing the 1-component.
[0200] Comparative Preparation Example 4-2
[0201] (1) Preparation of a single-component formulation
[0202] An acrylic mixed resin was prepared by mixing an acrylic copolymer resin, an epoxy acrylate resin represented by the following chemical formula, and trimethyl-2,4-pentanediol-1,3-isobutylate. At this time, the acrylic copolymer resin is a copolymer prepared by copolymerizing glycidyl methacrylate, methyl methacrylate, 4-cyanovaleric acid, and methyl methacrylate in a molar ratio of 1:2.20:0.25.
[0203] [Chemical Formula]
[0204]
[0205] In chemical formula 1-1, R 1 silver and R2 is and R 3 is a hydrogen atom, and R4 is -C(CH2CH2OCH=CH2)3, n is a number satisfying the weight-average molecular weight of the compound of 15,000 to 18,000, and * indicates a bonding site.
[0206] A one-component formulation was prepared by mixing 38.4 wt% of the above acrylic mixed resin, 2.9 wt% of hydroxyethyl methacrylate phosphate (binding promoter), 1.6 wt% of the physical property enhancer represented by Chemical Formula 3-1 of Example 4-1, 1.7 wt% of n-dodecyltriethoxysilane (powdered silicone water repellent), 0.3 to 0.6 wt% of neopentyl glycol (shrinkage inhibitor), 0.2 to 0.5 wt% of tributyl phosphate (defoamer), and the remaining amount of 100 wt% of an inorganic binder.
[0207] (2) Preparation of a two-component formulation
[0208] A two-component curing agent was prepared by mixing 38.4 wt% ammonium persulfate, 6.5 wt% phosphate, 4.3 wt% polyether-modified polysiloxane, and the remaining amount of water out of 100 wt%.
[0209] A 1-component and a 2-component were prepared in the same manner as in Preparation Example 4-1 above, but the 1-component was prepared without using a binding promoter and a shrinkage inhibitor when preparing the 1-component.
[0211] Experimental Example 2: Measurement of Compressive Strength of Two-Component Acrylic Waterproofing Grout Material
[0212] Acrylic waterproof grout materials were prepared by adding the first and second components prepared in Preparation Example 4-1, Comparative Preparation Example 4-1, and Comparative Manufacturing Example 4-2, along with water, to a stirrer in a weight ratio of 1:0.15:0.33, and then the compressive strength of these grout materials was measured according to KS F 4044, and the results are shown in Table 3 below.
[0213] division Preparation Example 4-1 (Mpa) Comparative Preparation Example 4-1 (Mpa) Comparative Preparation Example 4-2 (Mpa) 5 hours 3.50 ~ 4.00 3.62 ~ 4.10 2.83 ~ 3.00 10 hours 7.30 ~ 7.70 7.20 ~ 7.60 6.95 ~ 7.10 15 hours 9.80 ~ 10.20 9.30 ~ 9.80 8.50 ~ 9.40 20 hours 12.30 ~ 12.50 11.90 ~ 12.10 10.30 ~ 10.50 24 hours 12.70 ~ 13.00 12.50 ~ 13.00 12.35 ~ 12.55 3 days 14.20 ~ 14.50 13.20 ~ 13.60 13.80 ~ 13.95 7 days 20.20 ~ 20.50 17.60 ~ 17.90 19.30 ~ 19.80 28th 32.00 ~ 32.30 25.60 ~ 26.30 32.20 ~ 32.40
[0214] Looking at the rate of change in compressive strength over time in Table 3 above, Preparation Example 4-1, Comparative Preparation Example 4-1, and Comparative Preparation Example 4-2 all showed excellent compressive strength of 12 MPa or higher after 24 hours. However, Comparative Preparation Example 4-1, which did not use a binding promoter and a shrinkage inhibitor in the one-component formulation, showed relatively superior initial compressive strength compared to Preparation Example 4-1 and Comparative Preparation Example 4-2, but the compressive strength decreased compared to Preparation Example 4-1 from the point of 10 hours, and compared to Comparative Preparation Example 4-2, the compressive strength of Comparative Preparation Example 4-2 increased significantly from the point of 3 days.
[0215] In addition, when compared to Comparative Preparation Example 4-2, a conventional two-component acrylic grout material, Preparation Example 4-1 showed overall superior initial compressive strength, which is attributed to the difference in the acrylic mixed resin and bonding promoter components within the one-component material.
[0217] Experimental Example 3: Measurement of Water Absorption Amount of Two-Component Acrylic Waterproofing Grout Material
[0218] After preparing an acrylic waterproof grout material by adding the first component, the second component, and water prepared in Preparation Example 4-1 to a stirrer in a weight ratio of 1:0.15:0.33, the water absorption amount of the grout material was measured according to KS F 4919, and the results are shown in Table 4 below.
[0219] At this time, the control group used a backfill grout material prepared by mixing 100 parts by weight of ordinary Portland cement, 50 parts by weight of fly ash, 20 parts by weight of bentonite, 1 part by weight of a dispersant, 1 part by weight of wood scraper, and 0.15 parts by weight of water as a conventional backfill grout.
[0220] For the measurement method, a 5cm × 5cm × 16cm mold was constructed in two layers, and each layer was compacted and cured for one day in a constant temperature and humidity chamber (temperature 21±2℃, relative humidity 60%). After demolding, the molds were cured in the constant temperature and humidity chamber for up to 14 days. After 14 days of curing, the weight of the molds was measured to the nearest 1 / 100g, and after immersion in water (temperature 20±2℃) for 24 hours, the weight of the molds was measured to the nearest 1 / 100g. The amount of water absorbed was calculated using the following formula.
[0221] [ceremony]
[0222] Absorption amount (g) = Mold weight before immersion (g) - Mold weight after immersion (g)
[0223] As a result of the evaluation, the water absorption of the grout of the present invention was measured to be 0.2g, 0.2g, and 0.4g when the water usage was 39%, 40%, and 41%, respectively. In contrast, the water absorption of the control group was measured to be 2.1g, 2.2g, and 2.4g.
[0224] Through this, it was confirmed that the two-component acrylic waterproof grout material of the present invention prepared in Preparation Example 4-1 has excellent water repellency and waterproofing properties.
[0226] Preparation Examples 4-2 ~ 4-3 and Comparative Preparation Examples 4-3 ~ 4-4
[0227] A 1-component and a 2-component mixture were each prepared with the same composition as in Preparation Example 4-1 above, but with the content of the 1-component component varied as shown in Table 4 below, and a 2-component acrylic waterproofing grout material was prepared, and Preparation Examples 4-2 to 4-3 and Comparative Preparation Examples 4-3 to 4-4 were carried out.
[0229] Experimental Example 4: Waterproofing and Durability Evaluation
[0230] (1) A test specimen measuring 100 mm in height × 300 mm in width × 300 mm in length was prepared, simulating a concrete structure. Then, the center of the test specimen was assumed to be the crack area, and the construction area was washed with water and pre-treated. Afterward, the crack area was drilled to the back, and a packer was installed in the drilled hole. Then, the back waterproofing liquid (two-component acrylic waterproofing grout material, 1-component:2-component:water = 1:0.15:0.33 weight ratio) prepared in Preparation Example 4-1 was injected under high pressure through the packer to repair the crack area, and then the packer was removed. The construction area was finished with quick-setting cement paste to complete the waterproofing method.
[0231] After drilling the test specimen and installing the packer in the same way, the back-surface waterproofing liquid of Preparation Example 4-2, Preparation Example 4-3, Comparative Preparation Example 4-3, and Comparative Preparation Example 4-4 was repaired in the same way, the packer was removed, and the construction site was finished with quick-setting cement paste to complete the waterproofing method.
[0232] (2) To evaluate the waterproofing and durability of the concrete specimens with completed waterproofing, a concrete specimen with completed waterproofing was prepared by removing the quick-setting cement paste finish from the construction site, and a water permeability test was performed in accordance with KSF 4919. Specifically, the entire surface of the specimen, excluding the repaired areas on the front and back, was completely sealed with a silicone-based sealant, fixed to a permeability test device, and a water permeability evaluation 1 was performed in accordance with the standard test criteria of applying a water pressure of 0.3 MPa for 3 hours. Afterward, the specimen was separated and lightly wiped with Type B filter paper for 10 seconds in accordance with KSM 7602, and the center of the repaired area of the specimen was divided into two parts to visually check whether water had penetrated. ○ was marked if water had not penetrated, and × was marked if water had penetrated.
[0233] In addition, for the examples where water did not penetrate, an evaluation of water permeability in extreme conditions 2 was additionally performed by modifying the test standard to apply a water pressure of 1.0 MPa for 3 hours based on another prepared test specimen. Afterward, the test specimen was separated and lightly wiped for 10 seconds with Type 5 B filter paper in accordance with KSM 7602. Then, the center of the repaired area of the test specimen was divided into two sections, and water penetration was visually checked. ○ was marked if water did not penetrate and × if water penetrated. If penetration occurred, the penetration depth was measured with a ruler, and the results were presented together. In this case, if the result of the evaluation of water permeability in extreme conditions 2 was excellent, it indicates that water permeability was maintained under greater water permeability evaluation conditions despite the evaluation of water permeability 1, and thus it can be evaluated as having excellent waterproofing and durability.
[0234] Component 1 (Weight%) Preparation Example 4-1 Preparation Example 4-2 Preparation Example 4-3 Comparison Preparation Example 4-3 Comparison Preparation Example 4-4 acrylic mixed resin 42 37 42 32 50.5 Binding promoter 5.7 7.0 4.5 10.0 3.8 Physical property enhancer 1.6 1.6 1.6 1.6 1.6 water repellent 1.8 1.8 1.8 1.8 1.8 Anti-shrinkage agent 0.42 0.42 0.42 0.42 0.42 Antifoamer 0.3 0.3 0.3 0.3 0.3 Inorganic binder The remaining amount of 100 weight% My Pitcher Evaluation 1 ○ ○ ○ ○ × My Pitcher Evaluation 2 ○ × / 0.6㎝ ○ × / 2.5cm × / 1.3㎝
[0235] Looking at the waterproofing and durability evaluation results in Table 4 above, the backwater cutoff liquid (two-component acrylic waterproofing grout material) prepared in Preparation Examples 4-1 to 4-3 showed overall excellent waterproofing and durability evaluation results.
[0236] However, although Preparation Example 4-2 showed somewhat insufficient waterproofing and durability evaluation results in extreme environments (permeability evaluation 2), this level of evaluation result is considered excellent.
[0237] In contrast, Comparative Preparation Example 4-3, in which less than 35% by weight of acrylic mixed resin was used in the single-component formulation and an excessive amount of bonding promoter was used, showed results that were inferior in waterproofing and durability evaluations.
[0238] In addition, Comparative Preparation Example 4-4, which used more than 48% by weight of acrylic mixed resin in the one-component formulation and less bonding promoter, showed relatively lower waterproofing and durability compared to Preparation Example 4-3.
[0240] Example 1: Implementation of an inner surface waterproof acrylic back grouting composite reinforcement method for concrete structures
[0241] (1) Implementation of back grouting method
[0242] After identifying leaking cracks in the ceiling and walls of the underground parking lot, surface preparation was carried out to remove foreign matter from the cracks.
[0243] For ceiling waterproofing reinforcement, holes were drilled in the ceiling to the depth of the waterproofing layer, with one hole drilled every 0.5m. Additionally, injection packers were installed at each hole.
[0244] Next, the first component, the second component, and water of the two-component acrylic waterproofing grout material prepared in Preparation Example 4-1 were introduced into a stirrer and stirred in a weight ratio of 0.15:0.33 to produce an acrylic waterproofing grout material, and then injected under high pressure through an injection packer.
[0245] After the injection was completed and the packer was removed, the injection hole was sealed with high-viscosity epoxy resin and finished with paint.
[0246] In addition, for wall waterproofing reinforcement, holes were drilled to a depth of 200 mm in the wall surface, with one hole drilled every 0.5 m. Injection packers were installed at each hole.
[0247] Next, the acrylic waterproof grout material was prepared by adding the first component, the second component, and water, which are the two-component acrylic waterproof grout materials prepared in Preparation Example 4-1, to a mixer in a weight ratio of 1:0.75:0.33, and then injecting it under high pressure through an injection packer.
[0248] After the injection was completed and the packer was removed, the injection hole was sealed with high-viscosity epoxy resin and finished with paint.
[0249] (2) Implementation of guided waterproofing method
[0250] In the underground parking lot where the back grouting method was previously performed, after identifying damaged joints in the guide waterproofing panels, surface preparation was carried out to remove foreign matter around the damaged areas.
[0251] Next, the EVA-based coating material of Preparation Example 1 is applied using a roller at an application rate of 0.10 kg / m² 2It was applied first.
[0252] Next, the grid fiber reinforcement sheet of Preparation Example 3 was laminated and attached to the upper surface of the EVA-based coating material that had been applied as a first coat.
[0253] Next, the EVA-based coating material of Preparation Example 1 is applied to the upper surface of the grid fiber reinforcing sheet using a roller at an application rate of 0.18 kg / m² 2 The induction waterproofing method was performed by applying a second coat and curing it.
[0254] delete
[0255] delete
[0256] delete
[0257] delete
[0258] delete
[0259] delete
[0260] delete
[0261] delete Explanation of the symbols delete
Claims
Claim 1 A composite reinforcement method comprising a back grouting method and an induction waterproofing method, wherein the back grouting method comprises a process including: Step 1-1, preparing the surface of the construction area where cracks have occurred; Step 1-2, drilling and installing packers in the prepared construction area; Step 1-3, filling the inside of the cracks by injecting a back waterproofing liquid at high pressure through the packers; and Step 1-4, removing the packers after filling is complete and then performing a finishing treatment; wherein the back waterproofing liquid comprises a one-component formulation containing a curable component which is an acrylic resin mixture; A two-component acrylic waterproof grout material comprising a two-component mixture including a polymerization initiator and water; wherein the first component comprises an acrylic resin mixture comprising 35 to 48 wt%, a bonding promoter 4.0 to 8.0 wt%, a physical property enhancer 1.0 to 3.0 wt%, a powdered silicone water repellent 1.0 to 4.0 wt%, an anti-shrinkage agent 0.5 to 1.7 wt%, an anti-foaming agent 0.1 to 1.0 wt%, and the remainder of an inorganic binder among 100 wt%; wherein the acrylic resin mixture comprises, with respect to 100 wt% of an acrylic copolymer, 15 to 30 wt% of a diacrylate monomer represented by the following chemical formula 1 and 25 to 40 wt% of a glycidyl methacrylate; and wherein the acrylic copolymer comprises an alkyl (meth)acrylate having 1 to 2 carbon atoms, A random copolymer having a weight-average molecular weight of 6,000 to 12,000, copolymerized with 3-(trimethoxysilyl)propyl methacrylate and a ring-shaped structure-containing (meth)acrylate in a molar ratio of 1:0.4 to 0.6:0.8 to 1.0, wherein the ring-shaped structure-containing (meth)acrylate comprises one or more selected from the group consisting of cyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate, 4-tert-butylcyclohexyl acrylate, dicyclopentenyloxyethyl methacrylate and isobornyl acrylate, and 1-adamantyl (meth)acrylate, and the binding promoter comprises a phosphate-based compound and a compound represented by the following chemical formula 2 in a ratio of 1:1.5 to 3.An inner-wall waterproof acrylic back-surface grouting composite reinforcement method characterized by comprising at a weight ratio of 0, wherein the phosphate-based compound comprises one or more selected from hydroxyethyl acryloyl phosphate and hydroxyethyl methacrylate phosphate, and the two-component comprises a polymerization initiator including a persulfate compound, a reducing agent, an amine-based compound, an emulsifier, a stabilizer, and a solvent; [Chemical Formula 1]. In Chemical Formula 1, R 1 and R 2 Each is independent and is -CH2CH2CHCH2 or -CH2CH(CH2CHCH2)CH3.[Chemical Formula 2](R-CHOCH2CH2) n Si(CH2CH2CH2SO3H) m In Chemical Formula 2, R is C2 to C containing one or more double bonds. 10 straight-chain alkenyl groups or C3~C 10 It is a fragmented alkenyl group, n is an integer from 1 to 2, m is an integer from 2 to 3, and n+m is 4. Claim 2 delete Claim 3 The inner surface waterproof acrylic back grouting composite reinforcement method according to claim 1, characterized in that the inorganic binder comprises 10 to 20 parts by weight of hydrated lime and 20 to 30 parts by weight of calcium sulfoaluminate per 100 parts by weight of mixed cement containing ordinary Portland cement and alumina cement in a weight ratio of 1:0.4 to 0.
6. Claim 4 The inner surface waterproof acrylic back grouting composite reinforcement method according to claim 1, wherein the two-component mixture comprises 35 to 45 weight% of a polymerization initiator, 3 to 10 weight% of a reducing agent, 2 to 5 weight% of an amine-based compound, 2 to 6 weight% of an emulsifier, 5 to 10 weight% of a stabilizer, and the remainder being water, and wherein the amine-based compound of the two-component mixture comprises triethylamine and methylenedianylene in a weight ratio of 1:0.15 to 0.
2. Claim 5 In claim 1, the above-mentioned induction waterproofing method performs a process comprising: step 2-1 of preparing the construction surface of the joint; step 2-2 of applying an EVA (ethylene vinyl acetate)-based coating material to the prepared construction surface; step 2-3 of attaching a grid fiber reinforcement sheet to the upper surface of the construction surface coated with the EVA-based coating material; and step 2-4 of forming a finishing layer by applying an EVA-based coating material to the upper surface of the grid fiber reinforcement sheet; wherein the joint includes a joint of an induction waterproofing board, an inter-layer joint, a sash joint, or a structural joint; and wherein the grid fiber reinforcement sheet is a fiber sheet that has been needle-punched and grid-punched, and is characterized by having a plurality of fine holes formed by needle-punching and a plurality of cross-shaped holes formed by grid-punching arranged regularly or irregularly. Claim 6 A concrete structure waterproofing reinforcement system using an inner waterproof acrylic back grouting composite reinforcement method selected from any one of paragraphs 1 and 3 to 5.
Citation Information
Patent Citations
A waterproof reinforcement method of sub-terranean slab by injected double liquid type acrylic waterproof composition and waterproof reinforced connection structure of drain plate
KR1020250041664A
High-performance waterproofing method for maximizing crack prevention and moisture blocking performance using ultra-low viscosity acrylic waterproofing system
KR102865281B1